The effect of group categorization on injustice standards, harm judgements, collective guilt and motivated behavior - Herlache, Anne D. (My University, 2011)
This study focuses on whether or not participants' group categorization would impact the standards they used to judge future harm to an outgroup. In this case, harm is referring to current paper waste in university computer labs and the financial and stressrelated consequences this carries for future students. Also of interest is whether or not the participants' judgements of harm would impact collective guilt (the guilt felt on behalf of the ingroup) and if collective guilt would impact willingness to help the outgroup (i.e. engage in conservation of resources-proenvironmental actions). Participants in the inclusive condition (who saw themselves as part of a group including future students) were expected to set lower standards of harm (require less evidence to believe harm had been done), judge more harm had been done, feel more collective guilt, and be more willing to engage in proenvironmental actions, as compared to participants in the exclusive condition (current students only). The manipulation alone was not sufficient to impact the predicted variables; however, the interaction of the group categorization manipulation and level of group identification did differentially impact collective guilt and willingness to engage in proenvironmental actions in an unexpected way. Participants who were highly identified with their group and were in the exclusive condition felt more collective guilt and were more willing to engage in proenvironmental actions than participants who were less identified with their group. Implications of the findings are discussed in terms of changing proenvironmental behavior.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science-Psychology-Experimental
Keywords: Ethics; Responsibility; Intergroup relations; Group identity; Human behavior; Guilt